THE TERM “WESTERN UKRAINE” AND ITS “NATIONALIZING” FUNCTION IN THE DISCOURSE OF THE NEWSPAPER “DILO” (1923–1939) (Південний архів (історичні науки), 2022)
The purpose of this article is to investigate the use of the term “Western Ukraine” / “Western Ukrainian lands” as a “basic/key concept” in the discourse of Lviv’s newspaper “Dilo” and the environment of the Ukrainian National Democratic Union (UNDO) in 1923–1939. The study applies the methodology of “conceptual history” (Begriffsgeschichte) according to R. Koselleck and J. Ifversen. The article focuses on a specific aspect of the use of this term, namely its “nationalizing” function in the context of relations with the Polish state. For a broader comparative context, the article also briefly describes Ukrainian nationalistic, Polish, and Soviet discourses, as well as transcripts of sessions of the Sejm of the Polish Republic. The article shows that after the Entente Council of Ambassadors’ decision of 1923 to recognize the sovereignty of the Second Polish Republic over Eastern Galicia, the term “Western Ukraine” acquired a new geographical meaning in Ukrainian national and Soviet discourses, denoting the territory of all Ukrainian lands in Poland. Simultaneously, with the postulate of “autonomy of the western Ukrainian lands”, this term regained its political tone. The article shows that the term “Western Ukrainian lands” was used to emphasize the national character of the Ukrainian territories of Poland, to oppose it to the policy of the Polish state, and to connect this area with Greater / Soviet Ukraine. Because of such political connotation, this term provoked a sharp controversy between the Ukrainian and Polish discourses, in particular within the parliament. At the same time, with the change of political orientation in the 1930s, the use of the term “Western Ukrainian lands” in the political declarations of the UNDO and “Dilo” gradually decreased. The study concludes that the term “Western Ukrainian lands” became a “basic / key” concept in the interwar Ukrainian discourse and contained certain political connotations. This term’s “nationalizing” function and its sharp discursive role have led to the gradual refusal of its use at the highest political level.
Keywords: Western Ukraine, UNDO, Dilo newspaper, Second Polish Republic, interwar period, conceptual history